PENDAMPINGAN PENYUSUNAN SATGAS PENCEGAHAN DAN PENANGANAN KEKERASAN SEKSUAL (PPKS) - Yuniar Angelia Puspadewi; Jiarti Kusbandiyah; Dinda Oktia Maghfiroh (STIKES Widyagama Husada, 2025)
Any form of action that causes someone to feel insulted, harassed, humiliated and experience violence related to reproductive function, causing physical or psychological suffering and disrupting reproductive health is a resolution of sexual violence, the incidence of which is increasing from year to year. During the period of 2023, the Ministry of Women's Empowerment and Child Protection recorded 19,593 cases of violence in Indonesia. Women are more at risk of experiencing sexual violence than men with a percentage of 88.5%. Adolescents in the 13-17 age range are also a larger group experiencing violence by 38% compared to the 6-12 age group, 18-24 years and under 5 years of age. Physical violence is more common when compared to psychological violence, which is 43.8%.. This indicates that junior and senior high school age teenagers are the most victims of sexual violence. The number of cases of sexual violence in Malang Regency ranks first in East Java. In 2021 there were 125 cases reported and in 2022 up to July there will have been 135 cases, so it is estimated that this will increase by 50-100%. The number of sexual violence recorded is a reported incident, however, there are many cases that are not officially reported, which are called dark numbers, which have the potential to be higher than what is reported. This is due to the reluctance of victims to report due to the following factors: 1). Feelings of shame over the incident experienced because they are often blamed for the incident; 2). Unclear mechanisms regarding reporting cases of sexual violence; 3). Victims' distrust of the existing treatment system; 4). Not realizing that the incident was an act of sexual violence and 5). Fear of the risks that will be faced if the case is reported.